Failure analysis of two serial holes bolted joint hybrid composite - Sivakumar, Dhar Malingam; Selamat, Mohd Zulkefli; Ahadlin, Mohd Daud; Tan, CheeFai (2016)
This study investigates the effect of different geometry parameters to the behavior of bolted-joint hybrid composites. The hot compression method is used to fabricate the hybrid composite. The composites were fabricated with three layers of woven fibers which are two layers of woven glass fiber and a layer of woven kenaf fiber with polypropylene matrix making a composite panel. The nominal thickness of these composites is 3mm and the bearing test is done by using Universal Testing Machine. The test were conducted according to ASTM D5961. The results show the different geometry parameters affect the behavior of hybrid composites.